Governance Mechanisms and Improving the Performance of Local Authorities: Review of the Literature - Elmouaddine, Hanan; Alij, Noureddine (European Scientific Journal, ESJ, 2022)
Although the application of good governance the local government sector requires a profound administrative revolution affecting the behavior of all the players concerned, the issues of quality and excellence have forced local governments to change roles and responsibilities. In this context, this paper examines and synthesizes a literature review of the mechanisms of public governance to see to what extent the missions and purposes of this governance impact the performance of local authorities. To this end, the first part of this paper deals with a literature review on the concept of governance, its components, and its mechanisms in local authorities. The second part defines performance and its measurement tools in local authorities. In conclusion, the third part explores the impact of good governance on improving the performance of local authorities.